Rancang Bangun E-Comic Matematika Berbasis Pendekatan Karakter Terhadap Kemampuan Literasi Matematis Siswa SMP - Fransiska Lina; Utin Desy Susiaty; Yadi Ardiawan (LPD Universitas PGRI Pontianak, 2026)
The low mathematical literacy skills of junior high school students are linked to negative perceptions of mathematics and a lack of contextual, visual, and interactive learning media; meanwhile, character development is a crucial aspect that needs to be integrated into mathematics instruction. This study aimed to design and develop a character-based mathematics e-comic covering the topic of probability for eighth-grade junior high school students and to evaluate its validity, practicality, and effectiveness in enhancing students' mathematical literacy skills. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected via validation sheets from media and subject matter experts, teacher and student response questionnaires, and mathematical literacy tests, with a trial group consisting of 26 eighth-grade students from SMP Agape Pontianak. The results indicate that the developed e-comic was highly valid based on assessments by media experts (91.33%) and subject matter experts (94%), highly practical based on the average teacher and student responses (91.88%), and effective based on post-test results, achieving a mastery rate of 80.76% (21 out of 26 students met the Minimum Mastery Criteria). Thus, the character-based mathematics e-comic is suitable for use as an alternative learning medium to improve the mathematical literacy skills of junior high school students regarding the topic of probability